The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-35708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Facilitators and barriers to self-monitoring of blood glucose (SMBG) in diabetic patients visiting family medicine clinics at Akuh. 

Abstract: BACKGROUND: To determine factors that facilitate and are barriers to self-monitoring of blood glucose in type 2 diabetic patients visiting family medicine clinics at a tertiary care teaching hospital Karachi Pakistan. METHODS: Approximately 255 patients were consecutively recruited from the clinics during April 2018 to May 2019 at Family Medicine outpatient clinics at the Aga Khan University Hospital. Data on socio-demographic status, facilitators and barriers to SMBG were extracted through a questionnaire, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
0
0
Order By: Relevance
“…There was also no difference in the ability of participants to test and self-monitor blood glucose levels with only 35% from each group being able to test at home. This is similar to studies done in Nigeria which reported prevalence of selfmonitoring of blood glucose to range from 27% to 33% 21,22 . This can be attributed to the fact that most patients cannot afford a glucometer, test strips and needles.…”
Section: Discussionsupporting
confidence: 90%
“…There was also no difference in the ability of participants to test and self-monitor blood glucose levels with only 35% from each group being able to test at home. This is similar to studies done in Nigeria which reported prevalence of selfmonitoring of blood glucose to range from 27% to 33% 21,22 . This can be attributed to the fact that most patients cannot afford a glucometer, test strips and needles.…”
Section: Discussionsupporting
confidence: 90%
“…16,17 Similarly, studies conducted in Australia, USA, and Malaysia show that SMBG frequency is 88%, 32%, and 6.2%, respectively. 18 There is lack of evidence in this part of the world about the subject and its effects in terms of acute and chronic complications of diabetes mellitus. This study was conducted to assess the SMBG profile in both type 1 and type 2 diabetic patients, its frequency, adherence and non-adherence to SMBG.…”
Section: Discussionmentioning
confidence: 99%